Enantioselective Total Synthesis of Cymoside through a Bioinspired Oxidative Cyclization of a Strictosidine Derivative. (3rd December 2019) - Dou, Yingchao; Kouklovsky, Cyrille; Gandon, Vincent; Vincent, Guillaume
Abstract: The first total synthesis of the caged monoterpene indole alkaloid cymoside is reported. This natural product displays a unique hexacyclic‐fused skeleton whose biosynthesis implies an early oxidative cyclization of strictosidine. Our approach to the furo[3, 2‐ b ]indoline framework relied on an unprecedented biomimetic sequence which started by the diastereoselective oxidation of the indole ring into a hydroxyindolenine which triggered the addition of an enol ether and was followed by the trapping of an oxocarbenium intermediate. Abstract : Eine bioinspirierte oxidative Kaskadencyclisierung ermöglichte die erste Totalsynthese von Cymosid, einem Monoterpen‐Indolalkaloid mit einzigartigem, Furo[3, 2‐ b ]indolin‐haltigem, hexacyclischem Gerüst.